The Position of Localization Literature (1998-2024) in Türkiye - Dilruba Temuçin; Mehmet Cem Odacıoğlu; Atalay Gündüz (İstanbul Üniversitesi Çeviribilim Dergisi)
Localization is a (sub-)field within Translation Studies via the efforts of agents of localization who invest their capital and time in specializing within localization. This study aims to evaluate the development, position and significance of localization as a (sub-)field within Translation Studies in Türkiye. The research encompasses academic contributions from translation scholars, students, and other related disciplines, focusing on the evolution of localization literature since the 1990s. Methodologically, authors employ both quantitative and qualitative approaches, grounded in socio-cultural approaches and its notions like Bourdieusian translation sociology (agency) and Even-Zohar’s framework (culture planning) analyze the role of localization agents in enhancing cultural production and establishing a Turkish localization academic repertoire, namely, Turkish localization literature. Key findings indicate that Turkish localization literature has grown significantly since 2010s, with 125 studies identified, across various academic levels, with a notable emphasis on the interdisciplinary nature of localization, linking it to other interdisciplinary fields like Media Studies and Marketing. A significant portion of the literature focuses on various localization types and modes, including Video Game Localization, Website Localization, and Software Localization, showcasing diverse applications of localization practices in an academic discourse. Authors conclude that localization also serves as a critical tool for cultural planning and cultural advancement in Türkiye.